2011
DOI: 10.1111/j.1750-3841.2011.02144.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Hydrogen Peroxide and Radical‐Scavenging Activity of Raspberry during Osmotic, Convective, and Freeze‐Drying

Abstract: This study was conducted to investigate the influence of different drying treatments on antioxidant (AO) activity and phenolic content of raspberry (Rubus idaeus), cultivar Willamette. Whole raspberry fruits were dried convectively (air-drying), osmotically, and freeze-dried. Acetone-water extracts of fresh and dried raspberries were assessed for total phenolic content by standard Folin-Ciocalteau method. Two AO assays were applied, a recently developed direct current (DC) polarographic assay based on decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 34 publications
(45 reference statements)
2
23
0
Order By: Relevance
“…However, the increase resulted in an increase in the darkness of the dried mandarin, but the vitamin C content was not affected. Novakovic et al (2011) confirmed the superiority of freeze-drying in terms of the retention of phenolic compounds in the case of raspberry fruit. Convective drying resulted in slight changes, whereas osmotic dehydration showed a significant decrease of phenolic compounds and antioxidant activity.…”
Section: Recent Developments In Osmotic Dehydrationsupporting
confidence: 79%
“…However, the increase resulted in an increase in the darkness of the dried mandarin, but the vitamin C content was not affected. Novakovic et al (2011) confirmed the superiority of freeze-drying in terms of the retention of phenolic compounds in the case of raspberry fruit. Convective drying resulted in slight changes, whereas osmotic dehydration showed a significant decrease of phenolic compounds and antioxidant activity.…”
Section: Recent Developments In Osmotic Dehydrationsupporting
confidence: 79%
“…Therefore, the decrease in total phenolic content was mainly due the OD and was 75% to 77%. This decrease was also observed by Novaković et al [27] in a study OD of raspberries. According to them, the phenolic can migrate into the osmotic solution during the OD, inducing a loss of these compounds.…”
Section: Quality Of the Final Productsupporting
confidence: 68%
“…[26][27][28][29][30] This peroxide has the advantage of being sufficiently stable in cells, compared with other ROS that need to be produced "in vivo". The polarographic oxidation of hydrogen peroxide, from alkaline solutions, was used as the source of the peroxy-radical.…”
mentioning
confidence: 99%